12.35% efficient graphene quantum dots/silicon heterojunction solar cells using graphene transparent electrode. (January 2017) - Diao, Senlin; Zhang, Xiujuan; Shao, Zhibin; Ding, Ke; Jie, Jiansheng; Zhang, Xiaohong
Abstract: Zero-dimensional graphene quantum dots (GQDs) have lately intrigued intensive interest because of their great promise in energy, optoelectronic, and bio-imaging applications. Herein, we demonstrated the fabrication of highly efficient GQDs/n-silicon heterojunction solar cells via a simple solution process. Owing to the unique band structure, the GQDs layer could not only serve as hole transport layer to facilitate the separation of photo-generated electron-hole pairs, but also act as electron blocking layer to suppress the carrier recombination at anode. Moreover, graphene was used as the transparent top electrode for the heterojunction solar cells, ensuring the efficient light absorption and carrier collection. By adjusting the sizes of GQDs and the thickness of GQDs layer, a power conversion efficiency (PCE) as high as 12.35% under AM 1.5G irradiation was achieved, which represented a new efficiency record for this new-type solar cell. The devices also exhibited excellent stability in air due to the high chemical/physical stability of GQDs and graphene. The successful achievement of the high-efficiency GQDs/Si heterojunction solar cells opens up the opportunities for their potential applications in high-performance and low-cost photovoltaics. Graphical abstract: Highlights: GQDs/Si heterojunctions were constructed via a simple drop-casting method. Graphene layer was adopted as transparent electrode to ensure the efficient light absorption and carrier transportation. A recorded high power conversion efficiency (PCE) of 12.35% was achieved.